1987
DOI: 10.1016/s0735-1097(87)80342-x
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive measurement of coronary artery blood flow using combined two-dimensional and Doppler echocardiography

Abstract: Noninvasive measurement of left anterior descending coronary artery flow was attempted in 20 normal subjects and 80 patients with cardiovascular disease (valvular heart disease in 34, ischemic heart disease in 26, cardiomyopathy in 15 and other diseases in 5) using combined two-dimensional and Doppler echocardiography. A tubular structure about 2 mm in diameter containing Doppler flow signals was identified in the anterior interventricular sulcus in 7 (35%) of the normal subjects and 40 (50%) of the patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
47
1

Year Published

1992
1992
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 104 publications
(48 citation statements)
references
References 11 publications
0
47
1
Order By: Relevance
“…There are controversies regarding some variables measured by Doppler, but the integral of the mean velocity/time (VTI) is well accepted as an indicator of patency [6][7][8][9][10][11][12][13].…”
Section: Dvti = Diastolic Average Velocity-time Integral; Df = Diastomentioning
confidence: 99%
See 3 more Smart Citations
“…There are controversies regarding some variables measured by Doppler, but the integral of the mean velocity/time (VTI) is well accepted as an indicator of patency [6][7][8][9][10][11][12][13].…”
Section: Dvti = Diastolic Average Velocity-time Integral; Df = Diastomentioning
confidence: 99%
“…LITA has the ability to restore its patency after apparent occlusion in the progression of the coronary disease. Other conditions can influence LITA flow, including severe dysfunction of the left ventricle [6], coronary microcirculation disease, hypertrophy, fibrosis and myocardial viability [24,25]. TDE at stress can be very helpful in these situations and it can avoid a more invasive test [23].…”
Section: Dvti = Diastolic Average Velocity-time Integral; Df = Diastomentioning
confidence: 99%
See 2 more Smart Citations
“…Since the initial coronary flow study with TTDE by Fusejima,10 TTDE has been applied to evaluate many aspects of coronary pathophysiology, including epicardial coronary stenosis, 13,14 coronary vasodilatory function, [15][16][17][18] coronary obstruction with collateral flow, 19 and intramyocardial small coronary artery flow dynamics. 12,20 The present study confirmed the feasibility of TTDE to evaluate coronary pathophysiology and further demonstrated its utility to differentiate TIMI 0 to 2 and TIMI 3 reperfusion in patients with anterior AMI.…”
Section: Relation To Previous Studiesmentioning
confidence: 99%